Distal femur nonunion treated with retrograde intramedullary nailing and RIA: a case report - Pogliacomi, Francesco; Artoni, Carlotta; Calderazzi, Filippo; Leigheb, Massimiliano; Primiceri, Paolo; Pedrazzini, Alessio; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2020)
The current treatment of distal femur fractures includes locking plating and retrograde intramedullary nailing. These fractures are difficult to manage also for experienced surgeons, with results not always satisfactory. Reported nonunion rates now range from 0 to 34%. Factors associated with nonunion include comorbidities, such as obesity and diabetes, as well as the presence of open fractures, medial bone defects and comminuted fractures. This case report summarizes all of these assumptions and it concerns a 58 years old patient who underwent to 6 surgical procedures before to arrive to bone healing.